Enhancing the performance of pyridyl carboxamide-N,N-dimethyl amino chalcone (PCC) as a dye sensitizer for dye-sensitized solar cells (DSSCs) through the incorporation of electron donor moieties - Nassar, Maadh F.; Abdulmalek, Emilia; Ismail, Mohd F.; Alang Ahmad, Shahrul Ainliah (Elsevier, 2024)
This study has focused on enhancing the performance of pyridyl carboxamide-N,N-dimethyl amino chalcone (PCC) as a sensitizer for dye-sensitized solar cells (DSSCs) by strategically incorporating electron donor moieties identified in a literature review. Our reviewing the previous reports highlights the pivotal role of electron donors in optimizing light harvesting, electron injection, and overall power conversion efficiency in organic dye sensitizers, particularly those following a donor-bridge-acceptor (D-π-A) architecture. The selected donor moieties, including dithieno[3,2-b:2′,3′-d]thiophene (DTT), benzodithiophene (BDT), triphenylamine (TPA), carbazole (CBZ), and triazatruxene (TAZ), are systematically introduced into the molecular structure of PCC (abbreviated as PCC-DTT, PCC-BDT, PCC-TPA, PCC-CBZ, and PCC-TAZ, respectively). The performance of these modified compounds is rigorously evaluated using density functional theory (DFT) methods. Validation results revealed that the most reliable method for PCC derivative characterization involved the combination of the functional B3PW91 with a 6-31G(d) basis set. The results indicate that the incorporation of certain donor moieties, particularly BDT, significantly enhances the electronic and optical properties of PCC, including lower HOMO energy levels, a narrow energy gap (Egap), enhanced absorption intensity, and a redshift in absorption peaks. Evaluation of photovoltaic properties including electron injection (ΔGinj), and open circuit voltage (Voc), indicated facilitating spontaneous electron injection from the dyes to the TiO2 conduction band. Notably, PCC-TAZ demonstrated the lowest electron regeneration (ΔGreg), suggesting a notable potential for efficient electron regeneration.